Improving the Competence of Teachers in Writing Scientific Papers Through Mentoring Methods at the Senior High School/MA in Sungai Raya District - Dada Suhaida; Yuliananingsih Yuliananingsih; Fety Novianty; Hadirianto Hadirianto (International Journal of Public Devotion, 2022)
The activity of dedication of society is carried out with the aim of increasing teachers’ understanding towards writing scientific papers and motivating teachers to be active in writing scientific papers. This activity will be held on September 2, 2021, at SMA Negeri 2 Sungai Raya, Kubu Raya Regency. The method used in the implementation of this PkM is assistance in writing scientific papers and creating an account on the Publications page of OJS. There are various steps in implementing this PkM, that are: 1) an initial survey, with the aim of obtaining information about teachers' understanding of scientific writing, 2) The team prepares a PkM implementation plan which includes determination of the activity of the schedules, the activity of locations, the activity of participants, and resource persons. In preparation for this PkM, the team also coordinates and collaborates with related schools in determining participants who will take part in training to increase teacher competence in writing scientific papers with mentoring methods. Based on the results of the implementation of this training, it was obtained information that this mentoring method was considered in accordance with the needs of the teachers, this training activity received a positive response by the teacher participants, after participating in the training the teachers could write a journal article.